NASKAH LAKON SABAI NAN ALUIH KARYA TULIS SUTAN SATI: FENOMENA ANDROGINIK DALAM MASYARAKAT MATRILINEAL MINANGKABAU - Surherni Surherni (Puitika, 2019)
Tulis Sutan Sati Works “ Sabai Nan Aluih”: Androginic Phenomenon in Minangkabau Matrilinial Communuty. The aims of this research are 1) To know the cultural difraction of society in a drama text steming from the legendary story. 2) To know the understanding of matrilini concept in a drama text, 3) To know the way the author approaches women’s position in a story. This research employed gender studies to analyze the androginic phenomena of women figure in the text. The result the study shows that Tulis Sutan Sati does not give place to women as equal to men. Though culturally Minangkabau is matrilineal society, women remain sub ordinate to men as reflected in their literature.Keywords: androginik, matrilinial, drama text.